Youth Migration in Indonesia: Decision to Move and to Choose of Destination Areas - Meirina Ayumi Malamassam (Indonesian Journal of Geography, 2016)
Using intercensal population survey data, this paper examines migration behavior of youth in Indonesia aged 15 to 24 years old. Logistic regressions are employed to understand factors influencing youth’s decision to migrate as well as their choice of destination areas. The study findings suggest that migration preferences are determined by both the individual characteristics as well as the development level in both areas of origin and destination. It is also shown that education plays an important role in youth migration in Indonesia, not only in improving individual’s capacity to migrate, but also in prompting migration to big cities. In addition, youth migrants tend to move to areas with similar characteristics or similar cultural background to their areas of origin. For most of young people, migration is considered as an attempt for gaining upward social mobility, thus the prevalence of youth migration to less developed areas is low.